Fenomena Penggunaan Bahasa Gaul Dalam Percakapan Sehari-hari di WhatsApp Mahasiswa Universitas Al-Azhar Indonesia - Zahra Shafira Elfadia (LPPM Politeknik Pratama, 2023)
Language is an important thing in human life. Through humans can communicate with each other. In addition, language is used to convey ideas, ideas, opinions, feelings and thoughts to other people. As well as a tool to develop yourself and socialize with others. A language must have a clear meaning so that when there is communication there is no misunderstanding in the delivery. Currently there are several variations of language styles used in the community environment. The existence of variations in language style is triggered by the development of communication technology which is developing very rapidly. The development of this language makes the style of language used by generations to be different. Each generation will have its own distinctive language style. The use of Indonesian that is good and right is now starting to be displaced by slang and people feel used to using language. This study aims to describe the phenomenon of the use of slang in everyday conversations among university students. The method used in this research is qualitative with a descriptive approach.